Pemanfaatan Multimedia sebagai Media Penyuluhan Kesehatan Gigi - Hestieyonini Hadnyawati (Faculty of Dentistry, Universitas Indonesia, 2015)
The effort of suppression promotion and preventive as practice principles of "paradigma sehat" are concept which announcement by Departemen Kesehatan Republik Indonesia in framework reach Indonesia Sehat 2010. This effort as well as possible to get done by everyone Indonesia peoples, with the holistic through way dental education. For this application dental education needed medium. Multimedia are application various medium which different for associate and serve information in form text, audio, chart, animation, and video. Multimedia find occupy somebody for keep 90% what he read, hear, se, mention and done. Using multimedia as dental education medium can be used CD/VCD multimedia module, multimedia presentation, and multimedia web. With this reminder, so using multimedia technology find service as alternative medium for public dental education.